Początki i rozwój szkolnictwa polskiego w Rumunii do 1939 roku - Radziszewska, Maria (Biuletyn Historii Wychowania, 2018)
Poles settled in present-day Romania in the fourteenth century. A subsequent influx of Polish settlers followed the fall of the Kościuszko Uprising. The aim of this study is to present the history of education in the Polish minority in Romania. The work focuses on showing various forms of educational and upbringing institutions from the early 19th century to 1939. In the analyzed period, the Poles organized mainly kindergartens and comprehensive primary and secondary schools in Bukowina (now northern Romania). They also made attempts at introducing the Polish language to teachers’ training institutions i.e. teachers’ training colleges for men and women. They established their own socio-educational societies and built Polish Houses in which they pursued a wide range of educational and cultural activities. In the Kingdom of Romania, Polish children could also attend (under certain conditions) Polish language classes in Romanian state schools. Owing to the Polish Schools in Romania, followed by the Polish School Association in Romania, Polish private education assumed various forms.